Levocetirizine Oral Disintegrating Tablet: A Randomized Open‐Label Crossover Bioequivalence Study in Healthy Japanese Volunteers. Issue 7 (20th March 2020) - Ino, Hiroko; Shiramoto, Masanari; Eto, Takashi; Haranaka, Miwa; Irie, Shin; Terao, Takumi; Ogura, Hirofumi; Wakamatsu, Akira; Hoyano, Keiko; Nakano, Atsushi
Abstract: Levocetirizine is classified as a second‐generation antihistamine. Levocetirizine is available for the treatment of allergic disorders such as allergic rhinitis and chronic idiopathic urticaria. This was a single‐center, single‐dose, open‐label, randomized, 2‐way crossover study in healthy Japanese male subjects consisting of 2 parts. Part 1 compared the bioavailability of levocetirizine oral disintegrating tablet (ODT) and levocetirizine immediate‐release tablet (IRT) taken with water in the fasted state in 24 subjects; all subjects completed this part of the trial. In part 2, the bioavailability of levocetirizine ODT without water was compared with that of levocetirizine IRT with water in the fasted state in 48 subjects; 47 subjects completed this part of the trial. Bioequivalence was demonstrated between levocetirizine IRT 5 mg and ODT 5 mg. The safety profiles were generally similar between levocetirizine ODT and levocetirizine IRT, with no serious adverse events, deaths, or adverse events leading to withdrawal reported during the study.